Preparation and Electrochemical Performances of BixSr1-xCo0.2Fe0.8O3 (x = 0.5, 0.6, 0.7) as Potential Cathode Material for Solid Oxide Fuel Cells - Bao, Weitao; Sun, Hong (Asian Journal of Chemistry, 2013)
A perovskite oxide BixSr1-xCo0.2Fe0.8O3 (BSCF, x = 0.5, 0.6, 0.7) is investigated as a cathode material for solid oxide fuel cells. The BSCF is prepared using solid state reaction method. The XRD shows the perovskite phase is formed at x = 0.5 and impurity phases are detected with x increasing. The area specific resistance value for the BSCF cathode is as low as 0.07 W cm2 at 750 ºC as x = 0.5. The electrolyte-supported fuel cell generates good performance with the peak power densities of 0.078, 0.057, 0.032 Wcm-2 at 750 ºC as x = 0.5, 0.6, 0.7, respectively.